Kajian Kuat Lentur dan Kuat Tekan Beton Dalam Kondisi Cold Joint Pada Beton Dengan Bahan Tambah Fly Ash - Gunawan, Ari, Dr. Mochamad Solikin,S.T.,M.T, Ir. H. Ali Asroni, M.T (2016)
At work of buildings made of concrete with the workmanship that time there must be a connection concrete casting that can result from the occurrence of blocking the pipe concrete pump, damage track mixer that can slow down the process of casting, distance batching plan with a location too far, and also because the capacity Batching Plan which can not meet the demand of the foundry. Forming a non-homogeneous concrete layer due to casting with a long time span between the initial layer with a layer of concrete the next. At the opening of the formwork will be visible groove in the concrete with a condition called cold joint. Fly ash has a high content of cementitious materials and have pozzolanik properties that are expected to improve the strength of concrete in cold conditions joint. Based on this, the study aims to determine the bending strength and compressive strength of concrete in cold conditions joint with added material fly ash as well as determine the effect of time between the foundry cast the old with the new cast. The percentage of fly ash are used by 30% of the cement. Sample preparation with some differences when tied (Setting Time) to cold joint is 0 minutes, 45 minutes, 75 minutes, 120 minutes and 180 minutes. Overview analysis of this study is the compressive strength of concrete cylinders with a specimen diameter of 15 cm and a height of 30 cm, whereas for flexural strength of concrete beams using a specimen with a width of 15 cm, 15 cm thick and 53 cm long. Concrete mix design method using the American Concrete Institute. After testing and research, so the result is that the concrete compressive strength test results maximum is reached under conditions of normal concrete amounted to 25.616 MPa. The addition of 30% fly ash does not increase the compressive strength of concrete so that the concrete compressive strength declines as the length of time the connection. The minimum compressive strength occurred in the addition of fly ash by 30% to 180 minutes connection time of 18.636 MPa. Flexural strength of normal concrete beam on concrete produces flexural strength of 8,400 MPa. Maximum concrete beam flexural strength of the observed variation is reached on addition of 30% fly ash with a connection time of 0 minutes at 9.956 MPa, an increase of 18,52 % than normal concrete, and after the addition of fly ash variation of 30% with a connection time of more than 0 minutes strength concrete tends to decrease. Thus, the longer it will lead to decrease of grafting concrete beam flexural strength. From the test results showed that the addition of fly ash does not increase the strength of concrete but the addition of fly ash increase flexural strength of concrete. The longer the time a concrete connection will further reduce the strength of concrete.